Hubungan Antara Stres Sekolah Dan Locus Of Control Dengan Prokrastinasi Akademik - , Azhar; , Dr. Taufik, M.Si; , Dr. Sri Lestari, S.Psi.,M.Si (2015)
The aim of this research is to know the relationship between school stress and locus of control with academic procrastination in students of vocational muhammadiyah 1 Sukoharjo. The population in this study totaled 187 in class of XI SMK Muhammadiyah 1 Sukoharjo. The data collection technique in this research used a purposive cluster random sampling, while data collection method in this study using scales consisting of the school stress scale, locus of control scale and academic prokrastinasi scale. Also used a multiple regression analysis supported by SPSS 16.0 Program for Windows. Based on the results of an analysis showed that there is a significant relation exists between school stress and locus of control with academic procrastination where school stress and academic procrastination have a medium category while locus of control has a very low category. The analysis results showed that correlation between school stress and locus of control with academic procrastination have a positive relationship around r = 0,732.Whereas between school stress variable and academic procrastination variable has a positive relationship based on the results of an analysis around r = 0,689 and between locus of control variable and academic procrastination around r = 0,321. Effective contribution of school stress and locus of control = 54,77%%. Keywords: school stress, locus of control, academic procrastination